Patterns of International Capital Flows and Productivity Growth: New Evidence. Issue 5 (November 2015) - MacDonald, Margaux
Abstract Recent evidence from developing and emerging economies shows a negative correlation between growth and net capital inflows, a contradiction to neoclassical growth theory. I provide updated and disaggregated evidence on the origins of this puzzle. An analysis of the components of capital flows and of gross portfolio positions shows that foreign direct investment is directed towards countries with the highest growth rates, but that portfolio investment outflows exceed these inflows. Liberalized capital accounts further exacerbate this pattern. My results suggest a desire for international portfolio diversification in liquid assets by fast‐growing countries lies at the heart of the puzzle.